Primary nasal tuberculosis: A case report - Stojanović Jasmina; Belić Branislav; Mitrović Slobodanka; Stanković Predrag; Stojanović Stevan; Erdevički Ljiljana; Živić Ljubica; Arsenijević Snežana (Vojnosanitetski Pregled)
Introduction. During the past two decades, tuberculosis (TBC) both pulmonary and extrapulmonary, has emerged to be a major health problem. Nasal tuberculosis is a specific inflammatory process which is, in most cases, joined by the inflammation of neck lymph nodes. Case report. Thirty-yearold man presented with shortness of breath through the nose and periodical headaches. Clinical examination showed signs of chronic rhinitis, with slight granular changes of nasal septal mucosa. Laboratory analyses were within the reference ranges. Nasal and throat swabs for bacteria and fungi were normal. Skin allergy testing to standard inhalatory allergens was positive. Computer rhinomanometry showed increased nasal resistance at medium difficulty level, on the right. Radiography of paranasal sinuses indicated chronic polysinusitis on the right. Anti-allergy therapy was prescribed. The patient came for checkup after a month with subjective deterioration and a neck tumefact on the right. Nasal endoscopy revealed the presence of dark red infiltrates with the 3 mm diameter on nasal septal mucosa, dominantly on the right, with small greyish nodules. This findings indicated a potential specific nasal inflammatory process. In the upper jugulodigastric area, on the left, painless tumefact 3 x 5 cm in size was palpated, it was mobile comparing to supra- and infrastructure, with unaltered skin above. The definite diagnosis was established on the basis of the results of nasal mucosa biopsy. After histopathological diagnosis was obtained, we started with antituberculosis therapy at once. Conclusion. Due to actual trends of TBC incidences, otolaryngologist should have in mind nasal TBC, when granulomatose lesions are found in nose.